LOGISTIC APPROACH TO INTERACTION BETWEEN AN AIRLINE AND A FUEL SUPPLIER - Bo, Wang (Proceedings of National Aviation University, 2016)
This article discusses optimization of jet fuel supply to airlines under conditions of the surge in jet fuel prices by forecasting of airline’s fuel demand and planning the interaction between an airline and fuel suppliers.